Violence from a psychological and theological perspective - Brînzea, Nicolae; Silivestru, George-Ștefan (Technium Social Sciences Journal, 2023)
As an instrument of shared hope, of care for others, the Church, by virtue of divine grace, must shape future generations to be true communities of peace, capable of living the word of the Gospel. Violence, aggressive behavior has both bio-physiological causes, but it is also a learned reaction; however, the will of man dominates over all and as the source of aggression we find the sin that produces an aggression on the person who commits it, but also on fellow humans and nature. Orthodox spirituality sees in a violent man, a sick man, his acquisition being a commandment, and this must be achieved through understanding and through the infusion of love.